Research correlation between wastewater indicators for operational control - Shatokhina, Y.; Kovalev, O. (Енергетика і автоматика, 2015)
On the basis of studies of waste water. Slavutich developed image depends determining COD and suspended solids concentration by transparency for operational control of the cleaning process.